Modeling and Technology of Public Administration of Socio-Economic Security for Digitalization - Вдовічена, Лідія (International Journal of Management (IJM), 2020)
ABSTRACT The article explores the development prospects of the socio-economic security management considering the potential of digitalization as well as the elaborated strategies of public administration for the coming years. The definitions of digitization, social and economic security are systematized in the article. At the same time, the hierarchy of legal regulation is shown. This makes it possible to assess what legislation regulates economic and social security. It is substantiated that social and economic growth is possible not only under conditions of society development in a whole, but also under conditions of the national economy growth that includes the growth of gross domestic product and remuneration level along with the digitalization of the economy. The article examines the interdependence of various indicators, in particular, the impact of information and communication technologies on social and economic indicators of Ukraine's development level. The study of the dependence of socio-economic development level on the level of digitalization was also carried out. In particular, a correlation and regression analysis was conducted, which confirmed the high dependence between the above indicators. As a consequence, a model for forecasting the development of socio-economic status depending on the level of expenses on innovation of industrial enterprises was created. This model allows predicting the level of minimum wages in the country in line with changes in GDP and the costs of digitization. In order to promote the digitalization in Ukraine, the main strengths and risks the country may face during the implementation of these measures were identified. The article presents the main risks that can arise in the economy of the country during the transition to digitalization.
Keywords: Digitalization of Economy; Poverty Alleviation; Socio-economic Security